Between pandemics: sex worker, sexual minority, and transgender activism from HIV to COVID-19. Issue 12 (2nd December 2022) - Vijayakumar, Gowri; Panchanadeswaran, Subadra; Chacko, Shubha; Halford, Sarah J.; Subramaniam, Sanjitha
ABSTRACT: Public health crises alter political landscapes. This article investigates social movement strategies during and between the HIV and COVID-19 pandemics. We conducted a set of eighteen in-depth interviews with eleven leaders of organisations working with sex workers, sexual minorities, and transgender people around India, all of whom had been actively involved in HIV prevention programs, before and after the arrival of COVID-19 in India. First HIV, and then COVID-19, altered the political landscape for these groups in relation to three types of institutions: (1) donors (by creating dramatic increases and decreases in the amount, type, and conditions of global funding and deepening inequalities among organisations) (2) the state (by shifting the balance of advocacy and human rights work toward immediate relief); and (3) other social movements (by expanding solidarities across groups but also placing them in competition for limited resources). We argue that, to weather these dramatic shifts, organisations relied on internal alliances and resources built in and after periods of crisis. In this way, despite the differences between the two pandemics, the legacies of HIV shaped the response to COVID-19. Though responses to COVID-19 seem improvised and temporary, they build on a longer-term social movement infrastructure.